Ethicizing the Filipino concept of loob - Lat, Marlon Reyes (UP Los Baños Journal, 2017)
This article is an attempt to craft Filipino Ethics using the framework of Loob, a Filipino term literally means "interiority" or "innerness". However, in ethicizing the term "loob", it has several meanings depending on its contextual import. The first part of the article is a comparative analysis of Confucianism, Taoism, Buddhism as well as the term "Loob" in the domain of Ethics. The discussion focuses on the moral significance of Confucianism, Taoism, Buddhism and the Ethics of Loob to the human person and to the society. The other part of the article is the analysis of the Ethics of Loob using the five (5) traits of moral principles as discussed by James Fieser and Loius P. Pojman namely: prescriptivity, universalizability, overridingness, publicity and practicability.